Achieving efficient red room-temperature phosphorescence in two-dimensional hybrid halide perovskites by manganese doping - Zhu, Hui; Wang, Suqin; Sheng, Ming; Bo, Shao; He, Yu; Liu, Zhuang; Li, Min; Zhou, Guangtao (Frontiers in Chemistry, 2025)
Red room-temperature phosphorescence (RTP), characterized by its long emission wavelength and lifetime, has broad applications in various fields, including bioimaging, light-emitting diodes (LEDs), information encryption, and photodetectors. Two-dimensional (2D) hybrid halide perovskites are a novel class of organic-inorganic hybrid composite materials. Their diverse binary combinations offer a versatile platform for designing energy transfer pathway and introducing emerging optical phenomena, making them promising candidates for developing the next-generation of RTP materials. However, currently reported red RTP halide perovskites are scarce and often suffer from low quantum efficiency and short lifetime. Herein, we developed a series of 2D hybrid halide perovskites with efficient red RTP through doping manganese ions and found that the modified materials exhibit a significantly enhanced photoluminescence quantum yield of 66.38%, which is eight times higher than that of the original perovskite host. Moreover, the phosphorescence lifetime can be extended up to 12 ms. In-depth mechanistic investigations reveal that the exceptional luminescent performance originates from efficient energy transfer be-tween the host matrix and manganese ions. Furthermore, red-emitting LEDs have been successfully fabricated with these RTP materials as emitting layers, highlighting the promising applications of 2D hybrid halide perovskites in lighting applications.